Synoptic-scale drivers of long-term tropospheric ozone variability at Belgrano II station, Antarctica - J.A. Adame; M. Navarro-Comas; H. Ochoa; C. Prados-Roman; M. Yela (Atmospheric Research, 2026)

The haunting challenge of the trends and pathway assessments on newly introduced non-indigenous species in European seas - Okko Outinen; Peter A.U. Stæhr; Romeu S. Ribeiro; Aina Carbonell; Robert Comas-González; Lydia Png-Gonzalez; Maite Vázquez-Luis; Ann-Britt Florin; Rahmat Naddafi; Arjan Gittenberger; Hans Jakobsen; Ana C. Costa; et al. (Marine Pollution Bulletin, 2026)

The Lower to middle Jurassic of the Maláguide complex (Internal Zones, Betic Cordillera, S Spain) in Sierra Cabrera (Almería) and Cerro de San Antón (Málaga) - Juan C. Braga; Fernando Sola; María José Comas-Rengifo; Davide Bassi (Journal of Iberian Geology, 2025)
The lithostratigraphy, age and paleoenvironmental interpretation of Lower to Middle Jurassic carbonates in Sierra Cabrera (Almería) and Cerro de San Antón (Málaga city) add to the knowledge of the sedimentary evolution of the Maláguide Complex (Internal Zones, Betic Cordillera, southern Spain). In the Barranco de Azagador section in Sierra Cabrera, Sinemurian–Pliensbachian shallow-water carbonates show a mosaic breccia and a hardground at the top. The breccia matrix and the overlying deposits are reddish crinoid packstones with hardgrounds and ammonites late Pliensbachian in age. These features suggest an extensional breakup of an initial carbonate platform giving way to pelagic reduced sedimentation. Three overlying intervals of debris-fall breccias evidence deposition on or at the base of an escarpment. Clasts in the last breccia are Middle Jurassic oolites. In the Cerro de San Antón, shallow-water carbonates change upwards to several intervals of debris-fall breccias with clasts from underlying carbonates and a crinoid packstone matrix. Crinoid packstones with hardgrounds and late Pliensbachian-earliest Toarcian ammonites overlie the breccias. As in the Barranco de Azagador, the disintegration of the pre-late Pliensbachian carbonate platform was followed by pelagic sedimentation on or at the foot of an escarpment. The crinoid packstone is brecciated and covered with a red sandstone that also fills the spaces of laterally equivalent breccias, indicating emersion. Marine sedimentation was regained in the Middle Jurassic with ooid grainstones formed in shoals. The sedimentary evolution of both sections reflects the Pliensbachian rifting phase recognised in other areas of the Maláguide Complex, although the later evolution differs in the two study outcrops.

Can nitrogen availability impact plant performance under water stress? A review of traits, mechanisms, and whole plant effects - S. T. Drobnitch; T. C. Donovan; J. A. Wenz; N. E. Flynn; M. E. Schipanski; L. H. Comas (Plant and Soil, 2025)

Nitrogen and water availability affect soil nitrogen mineralization and maize nitrogen uptake dynamics - Tyler C. Donovan; Louise H. Comas; Joel Schneekloth; Meagan Schipanski (Nutrient Cycling in Agroecosystems, 2025)

Cytomegalovirus Infection Affects the Differentiation and Determines the Functionality of a Human Progenitor Neural Cell Line - H. M. González-Sánchez; E. I. Rubio Hernández; A. S. Silva-Ramírez; A. Miranda-López; A. E. Monsiváis-Urenda; M. Comas-García; D. E. Noyola; V. M. Rodríguez; C. G. Castillo (Current Microbiology, 2025)

Modeling MBR fouling: A critical review analysis towards establishing a framework for good modeling practices - V. Sandoval-García; M.V. Ruano; M. Alliet; C. Brepols; J. Comas; J. Harmand; M. Heran; G. Mannina; I. Rodriguez-Roda; I. Smets; A. Robles (Water Research, 2025)

Electro-responsive hyaluronic acid-based click-hydrogels for wound healing - Víctor Castrejón-Comas; Nil Mataró; Leonor Resina; David Zanuy; Quim Nuñez-Aulina; Joel Sánchez-Morán; Hamidreza Enshaei; Marc Arnau; Helena Muñoz-Galán; Joshua C. Worch; Andrew P. Dove; Carlos Alemán; et al. (Carbohydrate Polymers, 2025)

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

The removal of dissolved organic matter by marine sponges is a function of its composition and concentration: An in situ seasonal study of four Mediterranean species - M. Ribes; G. Yahel; C. Romera-Castillo; R. Mallenco; T.M. Morganti; R. Coma (Science of The Total Environment, 2023)

SWRO concentrates for more efficient wastewater reclamation - T. Sampedro; C. Tristán; L. Gómez-Coma; J. Rioyo; M. Sainz; I. Ortiz; R. Ibañez (Desalination, 2023)

Stochastic smoothing of point processes for wildlife-vehicle collisions on road networks - M. I. Borrajo; C. Comas; S. Costafreda-Aumedes; J. Mateu (Stochastic Environmental Research and Risk Assessment, 2022)
Wildlife-vehicle collisions on road networks represent a natural problem between human populations and the environment, that affects wildlife management and raise a risk to the life and safety of car drivers. We propose a statistically principled method for kernel smoothing of point pattern data on a linear network when the first-order intensity depends on covariates. In particular, we present a consistent kernel estimator for the first-order intensity function that uses a convenient relationship between the intensity and the density of events location over the network, which also exploits the theoretical relationship between the original point process on the network and its transformed process through the covariate. We derive the asymptotic bias and variance of the estimator, and adapt some data-driven bandwidth selectors to estimate the optimal bandwidth. The performance of the estimator is analysed through a simulation study under inhomogeneous scenarios. We present a real data analysis on wildlife-vehicle collisions in a region of North-East of Spain.

Differences between 1999 and 2010 across the Falkland Plateau: fronts and water masses - M. Dolores Pérez-Hernández; Alonso Hernández-Guerra; Isis Comas-Rodríguez; Verónica M. Benítez-Barrios; Eugenio Fraile-Nuez; Josep L. Pelegrí; Alberto C. Naveira Garabato (Ocean Science, 2017)
Decadal differences in the Falkland Plateau are studied from the two full-depth hydrographic data collected during the ALBATROSS (April 1999) and MOC-Austral (February 2010) cruises. Differences in the upper 100 dbar are due to changes in the seasonal thermocline, as the ALBATROSS cruise took place in the austral fall and the MOC-Austral cruise in summer. The intermediate water masses seem to be very sensitive to the wind conditions existing in their formation area, showing cooling and freshening for the decade as a consequence of a higher Antarctic Intermediate Water (AAIW) contribution and of a decrease in the Subantarctic Mode Water (SAMW) stratum. The deeper layers do not exhibit any significant change in the water mass properties. The Subantarctic Front (SAF) in 1999 is observed at 52.2–54.8° W with a relative mass transport of 32.6 Sv. In contrast, the SAF gets wider in 2010, stretching from 51.1 to 57.2° W (the Falkland Islands), and weakening to 17.9 Sv. Changes in the SAF can be linked with the westerly winds and mainly affect the northward flow of Subantarctic Surface Water (SASW), SAMW and AAIW/Antarctic Surface Water (AASW). The Polar Front (PF) carries 24.9 Sv in 1999 (49.8–44.4° W), while in 2010 (49.9–49.2° W) it narrows and strengthens to 37.3 Sv.

Dicephalous v. diprosopus sharks: record of a two‐headed embryo of G aleus atlanticus and review of the literature - V. Sans‐Coma; C. Rodríguez; M. A. López‐Unzu; M. Lorenzale; B. Fernández; L. Vida; A. C. Durán (Journal of Fish Biology, 2017)
As far as is known, this paper gives the first description of a two‐headed shark embryo belonging to an oviparous species, Galeus atlanticus (Carcharhiniformes: Scyliorhinidae). The specimen was detected among 797 embryos intended for cardiovascular studies, which represents a defect incidence of 0·13%. Each head had a mouth, two eyes, a brain, a notochord and five gill openings on each side. The two heads fused behind the gills. On the single body, there were four anticipated dorsal fins, two anterior, right and left and two posterior, right and left. Ventrally, the specimen possessed two pairs of pectoral fins, a pair of pelvic fins and one anal fin. Two adjacent notochords, two neural tubes and two dorsal aortas ran along the body, which bent 180° at its posterior portion. There were two hearts, two oesophaguses, two stomachs, two livers, but a single intestine with a spiral valve. Previous reports of conjoined twins in sharks are scarce and only refer to oviparous and ovoviviparous species. Seven dicephalous sharks reported so far were similar to the specimen described here, namely, with two totally separated heads on one body. Instead, only one case of diprosopus shark has been reported; it had a single body and a single head with partial duplication of the face. Two further cases described in the literature as dicephalous or simply as abnormal sharks should be better regarded as diprosopus, while another three cases, also considered dicephalous, showed a mixture of characteristics of diprosopia and dicephalia.

Experimental early pathogenesis of S treptococcus agalactiae infection in red tilapia O reochromis spp. - C A Iregui; J Comas; G M Vásquez; N Verján (Journal of Fish Diseases, 2016)
Streptococcus agalactiae causes a severe systemic disease in fish, and the routes of entry are still ill‐defined. To address this issue, two groups of 33 red tilapia Oreochromis spp. each of 10 g were orally infected with S . agalactiae ( n = 30), and by immersion ( n = 30), six individuals were control‐uninfected fish. Three tilapias were killed at each time point from 30 min to 96 h post‐inoculation ( pi ); controls were killed at 96 h. Samples from most tissues were examined by haematoxylin–eosin (H&E), indirect immunoperoxidase ( IPI ) and periodic acid‐Schiff; only intestine from fish infected by gavage was evaluated by transmission electron microscopy. The results of both experiments suggest that the main entry site of S. agalactiae in tilapia is the gastrointestinal epithelium; mucus seems to play an important defensive role, and environmental conditions may be an important predisposing factor for the infection.

Evaluation of antibiotic mobility in soil associated with swine-slurry soil amendment under cropping conditions - C. Domínguez; C. Flores; J. Caixach; L. Mita; B. Piña; J. Comas; J. M. Bayona (Environmental Science and Pollution Research, 2014)

The role of plasma IDO activity as a diagnostic marker of patients with colorectal cancer - M. Cavia-Saiz; P. Muñiz Rodríguez; B. Llorente Ayala; M. García-González; M. J. Coma-del Corral; C. García Girón (Molecular Biology Reports, 2014)

No effects of Bacillus thuringiensis maize on nontarget organisms in the field in southern Europe: a meta-analysis of 26 arthropod taxa - C. Comas; B. Lumbierres; X. Pons; R. Albajes (Transgenic Research, 2014)

Specificity and temporal dynamics of complex bacteria–sponge symbiotic interactions - Johannes R. Björk; C. Díez-Vives; Rafel Coma; Marta Ribes; José M. Montoya (Ecology, 2013)
Microbes are known to form intricate and intimate relationships with most animal and plant taxa. Microbe–host symbiotic associations are poorly explored in comparison with other species interaction networks. The current paradigm on symbiosis research stems from species‐poor systems where pairwise and reciprocally specialized interactions between a single microbe and a single host that coevolve are the norm. These symbioses involving just a few species are fascinating in their own right, but more diverse and complex host‐associated microbial communities are increasingly found, with new emerging questions that require new paradigms and approaches. Here we adopt an intermediate complexity approach to study the specificity, phylogenetic community structure, and temporal variability of the subset of the most abundant bacteria associated with different sponge host species with diverse eco‐evolutionary characteristics. We do so by using a monthly resolved annual temporal series of host‐associated and free‐living bacteria. Bacteria are very abundant and diverse within marine sponges, and these symbiotic interactions are hypothesized to have a very ancient origin. We show that host–bacteria reciprocal specialization depends on the temporal scale and level of taxonomic aggregation considered. Sponge hosts with similar eco‐evolutionary characteristics (e.g., volume of tissue corresponding to microbes, water filtering rates, and microbial transmission type) have similar bacterial phylogenetic community structure when looking at interactions aggregated over time. In general, sponge hosts hypothesized to form more intricate relationships with bacteria show a remarkably persistent bacterial community over time. Other hosts, however, show a large turnover similar to that observed for free‐living bacterioplankton. Our study highlights the importance of exploring temporal variability in host–microbe interaction networks if we aim to determine how specific and persistent these poorly explored but extremely common interactions are.

Analysing space–time tree interdependencies based on individual tree growth functions - C. Comas; L. Mehtätalo; J. Miina (Stochastic Environmental Research and Risk Assessment, 2013)

Cancer chemotherapy reduces plasma total polyphenols and total antioxidants capacity in colorectal cancer patients - R. Santiago-Arteche; P. Muñiz; M. Cavia-Saiz; C. Garcia-Giron; M. García-Gonzalez; Beatriz Llorente-Ayala; M. J. Coma-del Corral (Molecular Biology Reports, 2012)

Statistical inference for Gibbs point processes based on field observations - C. Comas; J. Mateu (Stochastic Environmental Research and Risk Assessment, 2011)

Intimal thickening of coronary arteries in the rabbitfish, Chimaera monstrosa L. (Chondrichthyes: Holocephali) - A C Durán; C Rodríguez; L Gil de Sola; B Fernández; J M Arqué; V Sans‐Coma (Journal of Fish Diseases, 2010)
This study is the first to report the occurrence of intimal thickening of coronary arteries in a holocephalan, namely the rabbitfish, Chimaera monstrosa . The sample studied consisted of five hearts from rabbitfish with body weights ranging between 12 g and 1116 g. The specimens were fixed in formalin, in methanol:acetone:water (MAW), or in paraformaldehyde and were examined by brightfield and polarization light microscopy. Coronary arteries from three larger animals displayed focal intimal thickenings, which were located in the left main coronary artery trunk, at the level of the cono‐ventricular junction, and in several intramyocardial ventricular arteries. The vascular changes were characterized by myointimal proliferation, breakage or absence of the inner elastic lamina, and, in one case, by increased collagen within the myointimal proliferation. Taking into account the severity of the coronary arterial changes, their location, and the body weight of the affected animals, we conclude that (1) these changes are age‐related in the rabbitfish and (2) local intense mechanical tension seems to be an important factor in their formation in this species.

Mass mortality in Northwestern Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2009)
Late in summer 2003, extensive mass mortality of at least 25 rocky benthic macro‐invertebrate species (mainly gorgonians and sponges) was observed in the entire Northwestern (NW) Mediterranean region, affecting several thousand kilometers of coastline. We were able to characterize the mortality event by studying six areas covering the main regions of the NW Mediterranean basin. The degree of impact on each study area was quantified at 49 sites by estimating the proportion of colonies affected in populations of several gorgonian species compared with reference data obtained in years without mortality signs. According to these data, the western areas (Catalan coast and Balearic Islands) were the least affected, while the central areas (Provence coast and Corsica‐Sardinia) showed a moderate impact. The northernmost and eastern areas (Gulf of Genoa and Gulf of Naples) displayed the highest impact, with almost 80% of gorgonian colonies affected. The heat wave of 2003 in Europe caused an anomalous warming of seawater, which reached the highest temperatures ever recorded in the studied regions, between 1 and 3 °C above the climatic values (mean and maximum). Because this exceptional warming was observed in the depth ranges most affected by the mortality, it seems likely that the 2003 anomalous temperature played a key role in the observed mortality event. A correlation analysis between temperature conditions and degree of impact seems to support this hypothesis. Under the present climate warming trend, new mass mortality events may occur in the near future, possibly driving a major biodiversity crisis in the Mediterranean Sea.

Characterising forest spatial structure through inhomogeneous second order characteristics - C. Comas; M. Palahí; T. Pukkala; J. Mateu (Stochastic Environmental Research and Risk Assessment, 2009)

Mass mortality in NW Mediterranean rocky benthic communities: effects of the 2003 heat wave - J. GARRABOU; R. COMA; N. BENSOUSSAN; M. BALLY; P. CHEVALDONNÉ; M. CIGLIANO; D. DIAZ; J. G. HARMELIN; M. C. GAMBI; D. K. KERSTING; J. B. LEDOUX; C. LEJEUSNE; et al. (Global Change Biology, 2008)

Effects of a mass mortality event on gorgonian reproduction - C. Linares; R. Coma; M. Zabala (Coral Reefs, 2008)

Genomic affinities between maize and Zea perennis using classical and molecular cytogenetic methods (GISH–FISH) - G. González; C. Comas; V. Confalonieri; C. A. Naranjo; L. Poggio (Chromosome Research, 2006)

Lack of molluscan host diversity and the transmission of an emerging parasitic disease in Bolivia - C. Meunier; C. Tirard,; S. Hurtrez‐Boussès; P. Durand; M. D. Bargues; S. Mas‐Coma; J. P. Pointier; J. Jourdane; F. Renaud (Molecular Ecology, 2001)
Fasciolosis is a re‐emerging parasitic disease that affects an increasing number of people in developing countries. The most severe endemic affects the Bolivian Altiplano, where the liver fluke ( Fasciola hepatica ) and its hermaphroditic snail host, Lymnaea truncatula, have been introduced from Europe. To achieve a better understanding of the epidemiological situation and the consequences of the colonization event of this invasive species, genetic analysis of Bolivian snail populations was needed. Here we compare the genetic diversity and population structure of snail samples from the Bolivian Altiplano with samples from the Old World at six polymorphic microsatellite loci. Whereas some variability exists in the snail populations from the Old World, we observe only a single genotype of L. truncatula in the Bolivian Altiplano. We discuss the possible explanations for such a reduction in genetic variability, and, given the high natural parasitism pressures exerted on the snail populations, we discuss the relevance of this result for host–parasite interactions.

Prey capture by a benthic coral reef hydrozoan - R. Coma; M. Ribes; C. Orejas; J.-M. Gili (Coral Reefs, 1999)